Rank Preservation and Reversal in Decision Making - Saaty, Thomas L. (Journal of Advances in Management Sciences & Information Systems, 2015)
There are numerous real life examples done by many people which show that the alternatives of a decision sometimes can reverse their original rank order when new alternatives are added or old ones deleted and without bringing in new criteria. There is no mathematical theorem which proves that rank must always be preserved and there cannot be because of real life and hypothetical counter examples in decision making methods. Rank preservation came to be accepted as the standard because of techniques that could only rate alternatives one at a time treating them as independent. Thus an alternative receives a score and it will not change when other alternatives are added or deleted. All methods that only rate alternatives one at a time, thus always preserving rank, may not lead to the right decision; even if they may be right in certain areas of application. In reality, to determine how good an alternative is on an intangible criterion needs experience and knowledge about other alternatives and hence in their evaluation, the alternatives cannot be completely considered as independent of one another.